Treatment of multiple adjacent gingival recessions using leucocyte- and platelet-rich fibrin with coronally advanced flap: a 12-month split-mouth controlled randomized clinical trial - KURU, LEYLA; DOĞAN, BAŞAK (My University, 2024)
Objective: This split-mouth randomized study aimed to assess efficacy of leucocyte-platelet-rich fibrin (L-PRF) versus connective tissue graft (CTG) in achieving root coverage (RC) for multiple adjacent gingival recessions (MAGRs) throughout 12-month period. Materials and methods: The study enrolled 59 teeth from 12 patients with Miller Class I MAGRs ≥ 2 mm on bilateral or contralateral sides. Patients were randomly assigned to receive coronally advanced flap (CAF) with either CTG (control) or L-PRF (test) treatment. Various parameters, including plaque and gingival index, clinical attachment level, recession depth, probing depth, recession width (RW), papilla width (PW), keratinized tissue width (KTW), gingival thickness (GT), percentage of RC, complete root coverage (CRC), and location of the relative gingival margin concerning the cemento-enamel junctions (GMCEJ) after CAF, were recorded at baseline, 3-, 6-, and 12-months post-surgery. On June 29, 2021 the study was registred to ClinicalTrials.gov (NCT04942821). Results: Except KTW and GT gain, all clinical parameters, RC, and CRC were similar between the groups at all follow-up periods (p > 0.05). The higher GT and KTW gains were detected in the control group compared to test group at 12 months (p < 0.05). Both RC and CRC were positively associated with initial PW and GMCEJ, but negatively with initial RW (p < 0.05). Conclusions: The current study concludes that L-PRF were equally effective as CTG in treating MAGRs in terms of RC and CRC. Additionally, RC and CRC outcomes appeared to be influenced by GMCEJ, PW, and RW. Clinical relevance: L-PRF could represent a feasible substitute for CTG in treating MAGRs.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; General Dentistry; Connective tissue; Gingival recession; Plastic surgery; Platelet-rich fibrin; Surgical flaps